Building telehealth teams of the future through Interprofessional curriculum development: a five-year mixed methodology study. Issue 1 (2nd January 2023) - DuBose-Morris, Ragan; McSwain, S. David; McElligott, James T.; King, Kathryn L.; Ziniel, Sonja; Harvey, Jillian
ABSTRACT: Building the next generation of telehealth enabled professionals requires a mixture of team-based, interprofessional practice with novel technologies that connect providers and patients. Effective telehealth education is critical for the development of multidisciplinary training curricula to ensure workforce preparedness. In this study, we evaluated the impact of a formal telehealth education curriculum for interprofessional students through an online elective. Over 12 semesters, 170 students self-selected to enroll in the 3-credit hour interprofessional elective and took part in structured didactic, experiential and interprofessional learning opportunities. Mixed-method assessments show significant knowledge and confidence gains with students reflecting on their roles as future healthcare providers. The results from five years' worth of course data shows not only an opportunity to advance the individual knowledge of trainees, but a larger movement to facilitate changes in practice toward population health goals. Recent global health events have further highlighted the need for a rapid response to public health emergencies by highly trained provider teams who are able to utilize technology as the cornerstone for the continuity of care.